Meningkatkan Keterampilan Guru dalam Pencegahan Kekerasan Anak Melalui Pendidikan Kesehatan Keluarga - Fifin Dwi Purwaningtyas; Ressy Mardiyanti; Suzana Dewi (LPMP Imperium, 2025)
The aim of this service is to improve children's mental and reproductive health, both physically and psychologically, while empowering the role of society through teacher education and increasing their understanding of children's sexuality education and reproductive health education. This training activity uses a training methodology, discussions, lectures, role playing and case discussions. The activity was carried out from August 15 to October 15 2024, with around 10 cadres attending. Based on monitoring and evaluation data carried out by the PKM program implementation team, it can be concluded that the PKM program is very beneficial for teachers. This is proven by the increase in participants' performance in answering Pretest and Posttest questions, which is proven by completing 10 questions. The PKM program implemented ran effectively without significant obstacles, as evidenced by the high enthusiasm of participants during the outreach activities. The results of this Community Service include increasing knowledge and understanding about Child Sexual Violence (KSA) and increasing the competence of cadres (teachers) to collaborate effectively with parents, local communities and related institutions that deal with child violence. In addition, there has been a marked increase in the ability of cadres to notify parents to remain alert to the potential for sexual violence crimes.